factories the following.
Attachments:
![](https://hi-static.z-dn.net/files/dbb/7c6b288715cb5b2b6e0fb0ae90081c12.jpg)
Answers
Answered by
24
Answer :
( x² - 2xy + y² ) - z² = ( x - y + z ) ( x - y - z )
Explanation :
( x² - 2xy + y² ) - z²
we know that, ( x - y )² = x² - 2xy + y²
•°• ( x² - 2xy + y² ) = ( x - y )²
=> ( x - y ) ² - ( z )²
We also know that, ( a² - b² ) = ( a + b ) ( a - b )
=> [ ( x - y ) + z ] [ ( x - y ) - z ]
•°• ( x² - 2xy + y² ) - z² = ( x - y + z ) ( x - y - z )
Hence, required expression is factorised.
Answered by
3
Question:
Factorise the given expression
Answer:
Step-by-step explanation:
Given expression
Further solving, we get
Concept Map:
Similar questions
Environmental Sciences,
6 months ago
Physics,
6 months ago
Math,
1 year ago
Physics,
1 year ago
Math,
1 year ago